2013
DOI: 10.1039/c2nj40693d
|View full text |Cite
|
Sign up to set email alerts
|

Study of the optical properties of a thermoresponsive polymer grafted onto porous silicon scaffolds

Abstract: International audienceIn this report, a polymer-filled porous silicon (pSi) structure is described that is able to detect changes in temperature around a critical value en route to developing a temperature sensor deployed in wounds dressings that signals inflammation or infection of the wound bed. Using surface-initiated atom transfer radical polymerization (SI-ATRP), thermoresponsive poly(N-isopropylacrylamide) (PNIPAM) chains are grafted onto pSi layers with different porosity and pore size and the optical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 34 publications
(46 reference statements)
2
47
0
Order By: Relevance
“…The surface chemistry of the samples was first analyzed by attenuated total reflectance–Fourier transform infrared (ATR‐FTIR) spectroscopy. The spectrum obtained for oxidized pSi (Figure (i)) showed a prominent peak at 1100 cm −1 that corresponds to the Si‐ O ‐Si symmetrical stretching peak of silica . Following deposition of the POct film (Figure (ii)), additional peaks at 1375 cm −1 , 1459 cm −1 , 2861 cm −1 and 3000 cm −1 were observed that correspond to the C−H stretching vibrations from the hydrocarbon‐rich polymer layer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface chemistry of the samples was first analyzed by attenuated total reflectance–Fourier transform infrared (ATR‐FTIR) spectroscopy. The spectrum obtained for oxidized pSi (Figure (i)) showed a prominent peak at 1100 cm −1 that corresponds to the Si‐ O ‐Si symmetrical stretching peak of silica . Following deposition of the POct film (Figure (ii)), additional peaks at 1375 cm −1 , 1459 cm −1 , 2861 cm −1 and 3000 cm −1 were observed that correspond to the C−H stretching vibrations from the hydrocarbon‐rich polymer layer.…”
Section: Resultsmentioning
confidence: 99%
“…IRS measurements can be used to observe changes in the EOT of the polymer‐modified pSi surface upon swelling or collapse of the polymer layer . Wu and Sailor demonstrated that the Fast Fourier Transforms (FFT) of pSi films coated with relatively thick capping polymer layers displayed two peaks with contributions from the pSi and from the pSi+polymer layers.…”
Section: Resultsmentioning
confidence: 99%
“…The porosity of the film was simulated from the reflectance spectra using the transfer matrix method [7,16,21], and oscillated between 68.5% and 78.3%. A thickness of 3,530 nm and pore sizes ranging from 25 to 45 nm in diameter were determined using scanning electron microscopy (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…While optical sensing based on the degradation of stimulus responsive polymer coatings on pSi has been reported, we show here for the first time the use of pSi as electrochemical transducer combined with the triggered degradation of polymer coatings for electrochemical sensing . The pSi‐THC electrode was coated with crosslinked HYAMA/PEGDA for the electrochemical sensing of the enzyme hyal that is secreted, e.g., by S. aureus .…”
Section: Introductionmentioning
confidence: 95%